Pemanfaatan Literasi Digital Dalam Meningkatkan Kreativitas Motorik Anak Berkebutuhan Khusus (ABK) - Alfirah, Alfirah; Gustiana, Zelvi (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2024)
ABK’s motor creativity is said to be good if they are in the right environment, surrounded by people who understand their special needs, both in terms of assisting, guiding and supporting no matter how small they do. Collaboration of digital learning and conventional creativity is one of the strategies developed by HSBE academically/non-academicly. The reading literacy ability of ABK is quite good in understanding writing, pictures, colors but due to verbal limitations it seems difficult to speak and not yet fluent in reading. The need for digital literacy for children with special needs in the form of visual art comics in the form of visualization of picture story books and visualization of digital fairy tales is quite influential in improving the motor skills of children with special needs. The computer science program was attended by ABK grades 2 and 3 because they were already able to operate basic computer systems. This study uses a qualitative descriptive method involving teachers, parents and children with special needs as a sample. The results of this study concluded that 2 children with special needs: 1ADHD – GAP (Attention Deficit Hyperactivity Disorder) and 1ASD – RRF (Autism Spectrum Disorder) have very low ratings in utilizing digital media compared to 3 other children with special needs so that they require extra assistance and learning media